(Invited) Microscopic Studies of Black Phosphorus and Its Field-Effect Transistors. (11th September 2015) - Pan, Minghu; Yuan, Hui; Xu, Ya-Qiong; Zhou, Zhixian; Meunier, Vincent
Abstract : In this manuscript, we report atomic scale studies of electronic direct bandgap measurement of the puckered honeycomb structure of freshly cleaved black phosphorus using a high-resolution scanning tunneling spectroscopy (STS) survey. Through a combination of STM/S measurements and first-principles calculations, a model for edge reconstruction and the related edge states are also determined. Besides, we also investigate electrical transport and optoelectronic properties of field effect transistors (FETs) made from few-layer black phosphorus (BP) crystals down to a few nanometers. In particular, we explore the anisotropic nature and photocurrent generation mechanisms in BP FETs through spatial- and polarization-dependent photocurrent measurements. Our results reveal that the anisotropic feature primarily results from the directional-dependent absorption of BP crystals.